Metal-Associated Biomarker Responses in Crabs from a Marine Protected Area in Southeastern Brazil - Araujo, G. S. [UNESP]; Gusso-Choueri, P. K. [UNESP]; Favaro, D. I.T.; Rocha, R. C.C.; Saint’Pierre, T. D.; Hauser-Davis, R. A.; Braz, B.; Santelli, R. E.; Freire, A. S.; Machado, W. T.V.; Cruz, A. C.F. [UNESP]; Abessa, D. M.S. [UNESP] (Springer Nature, 2020)
The environmental quality of a Ramsar wetland site located at the Cananéia-Iguape-Peruíbe Protected Area (CIP-PA), in São Paulo, Brazil, was assessed by geochemical analyses and biomarker assessments (GPx, GST, GSH, GST, MT, LPO, DNA damage) performed in swimming crab Callinectes danae Smith, 1869 organs (posterior and anterior gills and hepatopancreas) to estimate sediment contaminant bioavailability. The results indicated that two sampling stations, PT and PM, exhibited the worst environmental conditions, as sediments collected at both points contained metal contamination, while crabs exhibited significant responses for GPx, GST, and LPO (mostly during winter). Sediment contamination tended to be associated to fine sediments (both seasons) and organic matter (winter). During the summer survey, Pb concentrations in sediments of station PT exceeded the Brazilian Sediment Quality Guidelines (SQGs) and the Canadian Interim Marine Sediment Quality Guidelines. Metal concentrations in sediments sampled in winter were higher compared with summer, with Co, Ni, and Pb exceeding SQGs levels at PT, whereas Co, Ni, Hg, Zn, and Pb exceeded SQGs at PM. Biomarker induction during summer appeared to be caused by natural variables (water salinity and temperature, and molting cycle), whereas oxidative stress and tissue damage during winter appeared to be more clearly linked to metal contamination. Anterior gills presented the clearest signs of seasonal variability, being more responsive to sediment contamination. The results suggest that metals originated from the upper Ribeira de Iguape River are transported toward the estuarine system, causing effects on C. danae individuals. Additionally, seasonality is a strong factor concerning CIP-PA toxicity, since the rainfall regime significantly modifies the freshwater flow and, consequently, estuarine water salinity, suspended particle and metal inputs, as well as the location of depositional areas. Thus, efforts to mitigate CIP-PA contamination should be based on the control of upstream pollution sources.